Answer:
x = 7
Step-by-step explanation:
This is an isosceles triangle
This means two angles are identical
There are 2 angles with the size 9x-25
Now you should add all of the angles together
104 + 9x-25 +9x-25
Then simplify this
54 + 18x
You should know that angles in a triangle add up to 180
54 + 18x = 180
Subtract 54 from both sides
18x = 126
divide both sides by 18
x = 7
The formula is 2*3.14*r
so 2*3.14*6=37.68
Select all that apply
(0,6)
(-1,4)
(-1,-4)
(3,12)
Question 2:
Which ordered pairs are a solution to the equation y=4-2x
Select all that apply
(-1,2)
(0,4)
(-1,6)
(1,6)
Answer:
1.
(0,6)
(-1,6)
(3,12)
2.
(0,4)
(-1,6)
Step-by-step explanation:
The rule for the first question is y = 2x + 6
We can substitute the numbers for each equation.
6 = 2(0) + 6
6 = 6
So (0,6) is correct.
4 = 2(-1) + 6
4 = 4
So (-1,4) is correct as well.
-4 = 2(-1) + 6
-4 ≠ 4
(-1,-4) is incorrect.
12 = 2(3) + 6
12 = 12
So this answer is correct as well.
The second question‘s rule is that y = 4 - 2x. So we can substitute the numbers.
2 = 4 - 2(-1)
2 ≠ 6
This is incorrect.
4 = 4 - 2(0)
4 = 4
This answer is correct.
6 = 4 - 2(-1)
6 = 6
This answer is correct as well.
6 = 4 - 2(1)
6 ≠ 2
This answer is incorrect as well.
The expression that gives the train's speed in miles per hour is:
Speed = 524 / 4.5 = 116.44 miles per hour.
To find the train's speed in miles per hour, you can use the formula:
Speed (in miles per hour) = Distance (in miles) / Time (in hours)
In this case, the distance the train travels is 524 miles, and the time it takes is 4 1/2 hours. To convert 4 1/2 hours into a decimal, you can calculate it as follows:
4 1/2 hours = 4 + 1/2 = 4.5 hours
Now, you can use the formula to calculate the speed:
Speed (in miles per hour) = 524 miles / 4.5 hours
Speed (in miles per hour) = 116.44 miles per hour (rounded to two decimal places)
So, the expression that gives the train's speed in miles per hour is:
Speed = 524 / 4.5 = 116.44 miles per hour
To Learn more about Distance here:
#SPJ2
Answer:
15
Step-by-step explanation:
Square root of 5=√5
Square of the square root=(√5)^2
=5
Square root of 3=√3
Square of the square root=(√3)^2
=3
So (square root of 5)^2×(square root of 3)^2
5×3
15
Therefore the final answer is 15